100‐year‐old enigma solved: identification, genomic characterization and biogeography of the yet uncultured Planctomyces bekefii. (11th November 2019) - Dedysh, Svetlana N.; Henke, Petra; Ivanova, Anastasia A.; Kulichevskaya, Irina S.; Philippov, Dmitriy A.; Meier‐Kolthoff, Jan P.; Göker, Markus; Huang, Sixing; Overmann, Jörg
Summary: The first representative of the phylum Planctomycetes, Planctomyces bekefii, was described nearly one century ago. This morphologically conspicuous freshwater bacterium is a rare example of as‐yet‐uncultivated prokaryotes with validly published names and unknown identity. We report the results of molecular identification of this elusive bacterium, which was detected in a eutrophic boreal lake in Northern Russia. By using high‐performance cell sorting, P . bekefii ‐like cell rosettes were selectively enriched from lake water. The retrieved 16S rRNA gene sequence was nearly identical to those in dozens of metagenomes assembled from freshwater lakes during cyanobacterial blooms and was phylogenetically placed within a large group of environmental sequences originating from various freshwater habitats worldwide. In contrast, 16S rRNA gene sequence similarity to all currently described members of the order Planctomycetales was only 83%–92%. The metagenome assembled for P . bekefii reached 43% genome coverage and showed the potential for degradation of peptides, pectins, and sulfated polysaccharides. Tracing the seasonal dynamics of P . bekefii by Illumina paired‐end sequencing of 16S rRNA gene fragments and by fluorescence in situ hybridization revealed that these bacteria only transiently surpass the detection limit, with a characteristic population peak of up to 10 4 cells ml −1 following cyanobacterial blooms.